Simulation of vertical vibrations of the operator’s seat with a given force characteristic - Korytov M.S.; Sherbakov V.S.; Galdin N.S.; Kashapova I.E. (Научно-технический вестник Брянского государственного университета)
Operators of construction and road building machines are subjected to significant vibration and shock loads. Vibrations lead to occupational diseases and reduced working capacity of operators. The main areas of vibration protection are vibration-protective cab supports and vibration-protective seat suspensions. Active vibration protection systems have advantages in the breadth of frequency range and possibilities of their customization. At the same time, passive vibration protection systems are more reliable and durable. The effect of quasi-zero stiffness is utilized in promising vibration protection systems. The developed simulation mathematical model of passive vibration protection system of a seat in SimInTech environment is described. The model takes into account external influences in the form of specified displacements of the seat base, and system parameters. Input parameters are mass, time, stiffness and damping coefficients, amplitude and frequency of vibrations of the seat base. Output parameters are the coordinate, velocity and acceleration of the seat in the absolute coordinate system, and the derivative of them is the overload of the seat. Also as a result of modeling the time dependencies of the local coordinate, or deformation of the vibration protection mechanism are determined. In the SimInTech environment the blocks of the “Mechanics” library are used. The specified functional dependencies of the return force and damping are realized. The model reproduces vertical vibrations of the seat with the operator. An example of use and results are given. The return force is determined by a three-segment static force characteristic. The overload is determined from the current acceleration values of the seat, which in turn are determined by the virtual sensor unit. An example of using the model is given, when vertical vibrations of a seat with an operator of a ground transportation and technological machine are investi-gated. The base of the seat, i.e. the floor of the operator’s cabin, performs specified harmonic oscillations. Graphs of time dependences of the vertical coordinate of the seat center of mass, the vertical coordinate of the seat base and the displacement of the seat relative to its own base, as well as the time dependence of the seat overload are given. The field of application of the developed model is to study the dynamics of forced vertical vibrations of the vibration protection system of the seat of a ground transportation-technological machine with a human operator.